New results on Bullen-type inequalities for coordinated convex functions obtained by using conformable fractional integrals - Hezenci, Fatih; Kara, Hasan; Budak, Hüseyin (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 Our aim is to investigate novel Bullen-type inequalities for coordinated convex mappings by employing conformable fractional integrals. Initially, an identity incorporating the conformable fractional integrals was established to serve for this purpose. By using this identity, new inequalities аre derived expanding the scope of previously established results obtained with the help of Riemann–Liouville integrals by making specific choices of variable and applying the Hölder inequality and the power-mean inequality.